Essential Oils and Their Application in Food Safety - Maurya, Akash; Prasad, Jitendra; Das, Somenath; Dwivedy, Abhishek Kumar (Frontiers in Sustainable Food Systems, 2021)
Food industries are facing ry faces a great challenge due to contamination of food products with different microbes such as bacteria, fungi, viruses, parasites etc. These microbes deteriorate food items both by producing different toxins during pre and post-harvest processing. They not only deteriorate food but also contaminate them with different toxins. Mycotoxins are one of theamong most potent and well-studied toxic food contaminant of fungal origin causing severe health hazard to human health hazard. UseApplication of synthetic chemicals as food preservatives in food system pose a real scourge in the present scenario is being discouraged due to their bio-incompatibility, and non-biodegradability and environmental non-sustainability. Therefore, plant based antimicrobials including essential oils have developed cumulative interest come up as potential replacement alternative of these popular synthetic preservatives because of their ecofriendly nature and generally recognized as safe (GRAS) status. However, the practical Worldwide utilization of essential oils as plant based and efficient antimicrobial in the food industry is challenging due to their volatile nature, less solubility and high instability. The recent application of different delivery strategies viz. nanoencapsulation, active packaging and polymer based coating are effectively addressed these challenges and improve the bioefficacy as well as controlled release of essential oils. This challenge can be overcome by nanoencapsulation. Nanoencapsulation is an interesting and emerging technique that raises the physico-chemical properties, as well as slow release of essential oils for improving food safety. This article provides an detailed overview on essential oils for preservation of stored foods against bacteria, fungi and mycotoxins of antimicrobial plant based food preservatives, their along with specialized mechanismmode of action and technological advancement by using different delivery systems for their effective application in food and agricultural industries smart green preservative.in their application for food preservation.